Anti-tuberculosis drug development via targeting the cell envelope of Mycobacterium tuberculosis - Xu, Xinyue; Dong, Baoyu; Peng, Lijun; Gao, Chao; He, Zhiqun; Wang, Chuan; Zeng, Jumei (Frontiers in Microbiology, 2022)
Mycobacterium tuberculosis possesses a dynamic cell envelope, which consists of a peptidoglycan layer, a mycolic acid layer, and an arabinogalactan polysaccharide. This envelope possesses a highly complex and unique structure representing a barrier that protects and assists the growth of M. tuberculosis and allows its adaptation to the host. It regulates the immune response of the host cells, causing their damage. Therefore, the cell envelope of M. tuberculosis is an attractive target for vaccine and drug development. The components involved in the biosynthesis pathways of the cell wall are effective targets for many antimicrobial agents. This review mainly summarizes the development of drug enzymes involved in the biosynthesis of the cell wall in M. tuberculosis, and other potential drug targets in this pathway, to provide more effective strategies for the development of new drugs.